Dissertation of Medical Postgraduate Students: Do We Need Individual Dissertation or Group Dissertation? An opinion - Vallari Jadav; Anil Mahajan; Sahjid Mukhida (APIK Journal of Internal Medicine)
Medical postgraduate students (residents) must choose and complete individual dissertation topics to be eligible for the final examination within their post-graduation period. Resident must select a unique topic for the dissertation and work on that, which is difficult considering the number of research already done in the same institute with the same resources and a heavy workload. Giving a single dissertation topic between few genuinely interested persons may lead to better quality and authentic research by the residents. If we can go ahead with a combined dissertation between a few (2–4) residents which can be within the same department or interdepartmental collaboration, dissertation work can be divided and will not be a burden on a single person. It will decrease the quantity but will improve the quality of dissertations and research publications by residents. This newer idea can save time with resources. This practice can surely bring the research quality to the at par level, which is a necessity in today’s world.